English Language Teacher Professional Development During COVID-19 in Nepal - Gautam, Ganga Ram (Interdisciplinary Research in Education, 2021)
COVID-19 pandemic has brought a big pedagogical shift in education across the board. In this context, teachers expected to be adaptable in the new situation in by familiarizing themselves to the emerging technology-driven pedagogy. This article explores how 102 English language teachers in Nepal prepared themselves to respond to COVID-19 by attending various professional development events organized between April and September 2020 by different professional forums and organizations. The results show that English teachers in Nepal attended three kinds of events that include training programs to learn technology, events to learn about the online resources for English language teaching and professional development events to enhance their professional skills. Participation in these events made English teachers digitally confident to run the classes online and increased awareness of the integration of online resources in English language teaching.